RESULTS OF APPLYING THE ENIO SCORE IN PREDICTING EXTUBATION OUTCOMES IN PATIENTS WITH BRAIN INJURY (Vietnam Journal of Community Medicine, 2026)
BackgroundExtubation in patients with traumatic brain injury is a challenging clinical decision. Extubation failure increases the risk of pneumonia, prolongs mechanical ventilation duration, and increases mortality. Conventional weaning criteria do not adequately reflect airway protection ability and neurological recovery. The ENIO score integrates neurological and respiratory factors to support the prediction of extubation outcomes. However, the ENIO score has not been widely studied in Vietnam.ObjectiveTo analyze factors associated with extubation outcomes and evaluate the value of the ENIO score in predicting extubation success in patients with traumatic brain injury.MethodsA retrospective descriptive study was conducted at the Center of Anesthesia and Intensive Care, Bach Mai Hospital, from January 2025 to October 2025. The study included patients with brain injury, Glasgow Coma Scale (GCS) score ≤12, and invasive mechanical ventilation for more than 24 hours. Patients underwent extubation after successful weaning from mechanical ventilation. Outcomes were classified as successful or failed extubation within 5 days after extubation.ResultsAmong 111 studied patients, 75 patients (67.6%) had successful extubation, while 36 patients (32.4%) experienced extubation failure. Factors associated with successful extubation included strong cough reflex (81.3% vs. 33.3%; p
Keywords: ENIO score; extubation; traumatic brain injury; neurosurgical intensive care; extubation prediction.